The Role of Organizational Behavior in Creating Professional Human Resources - Kusairi, Kusairi; St. Rodliyah, St. Rodliyah; Fauzi, Imron (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
the purpose of this study is to find out in-depth information about the management of organizational behavior at Madrasah Tsanawiyah (MTs) Miftahul Ulum Al Azizah Sumberbaru Jember in 2022/2023 which is oriented towards creating professional human resources. In detail, the objectives of this study are described in the research focus including: 1). Describe the management of madrasah organizational behavior at MTs Mifathul Ulum Al- Azizah Year 2022/2023 in creating professional human resources , 2) Analyzing obstacles and solutions in the management of madrasah organizational behavior at MTs Mifathul Ulum Al- Azizah Year 2022/2023 in creating professional HR . The research method uses a qualitative approach with the research subject being the head of the madrasa and supported by teachers, students, deputy head of curriculum and school supervisors as informants. Data collection methods using observation, interviews and documentation as well as triangulation are still used as a foundation in seeking data validity. The results of this study reveal that 1). organizational behavior management of MTs Mifathul Ulum Al- Azizah Year 2022/2023 in creating professional HR is designed with several stages namely First, Planning which includes analyzing all activities or capacity activities intellectual , capability, work experience and exemplary. Second, Recruitment which includes prioritizing academic achievement, having good character and making achievement and professionalism a benchmark. Third, Development which includes scheduling training , workshops and training if necessary to increase the standard of ability or skills. Fourth, supervision which includes scheduled inspections of all madrasah resources. Fifth, evaluations that carry out scheduled reviews through monthly, midterm , end of semester or end of learning. 2) Barriers to Organizational Behavior Management at MTs Mifathul Ulum Al- Azizah Year 2022/2023 include teaching staff not meeting what is needed, not graduates from teacher education, teachers who have taught not according to their fields, lack of supervision, lack of capacity building, and lack of evaluation. Solution; recruitment management with academic and non-academic selection, development of training teachers, workshops, supervision and attention to the organization.